Boosting Enhancement of the Electron–Phonon Coupling in Mixed Dimensional CdS/Graphene van der Waals Heterojunction. Issue 11 (6th February 2022) - Li, Zhonglin; Guo, Shuai; Weller, Dieter; Quan, Sufeng; Yu, Jing; Wang, Runqiu; Wu, Mengxuan; Jiang, Jie; Wang, Yingying; Liu, Ruibin
Abstract: Electron–phonon coupling plays a key role in affecting the properties of the semiconducting nanostructures, such as providing the possibility for obtaining higher superconducting transition temperatures. Here, using Raman, temperature‐dependent and polarized Raman scattering measurements, ultra‐strong electron–phonon coupling in 1D CdS nanowires and 2D graphene heterostructures is demonstrated. The intensity ratio of 2LO/1LO mode in CdS nanowires provides a spectroscopy‐based method to quantify electron–phonon coupling, the strength of which is temperature and polarization dependent. The intensity ratio mode of 2LO/1LO in heterostructure reached up to 8.95 when the incident laser polarization is parallel to the c ‐axis of the nanowire. It is ≈2.37 times higher than in an individual nanowire. In addition, in situ and time‐resolved photoluminescence spectra demonstrate the dynamics of the exciton recombinations, providing a comprehensive understanding of the enhancement of electron–phonon coupling in heterostructures. Via optical waveguiding characterization, the graphene layer is demonstrated to not only be an ultrafast carrier transfer channel but also a low Fermi level channel that induces the formation of the built in electrical field, elevating the electron–phonon coupling. Such new mixed dimensional heterostructures illustrate a straightforward approach to enhance the electron–phonon coupling, which may be applied to many integrated superconducting photonic and optoelectronic devices. Abstract : Due to the formation of the built‐in electric field, the mixed dimensional 1D CdS nanowire/2D graphene van der Waals heterostructure shows strong electron–phonon coupling with the average intensity ratio of 2LO/1LO Raman mode is 1.2. Additionally, CdS nanowires are the typical polar semiconductor, the intensity of 2LO/1LO presents polarization dependence, and the maximum value can reach up to 8.95.